2006
DOI: 10.1002/hed.20326
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of head and neck squamous cell carcinoma: Promising signs in need of prospective evaluation

Abstract: Some progress has been made with respect to molecular markers and head and neck cancers. Translational and prospective, hypothesis-driven research must proceed with sufficient rigor to facilitate the clinical applicability of such results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
101
0
36

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 102 publications
1
101
0
36
Order By: Relevance
“…Several studies have shown that aneuploid tumours are more aggressive than diploid tumours in head and neck cancers (Hogmo et al, 1994;Rubio Bueno et al, 1998). Proliferative activity, as determined by expression levels of the Ki-67 nuclear antigen, has been linked to prognosis and treatment prediction with varying results in oral cancer, with few studies performed exclusively in OTSCC (Xie et al, 1999;Pich et al, 2004;Lothaire et al, 2006;Kim et al, 2007). The use of immunohistochemistry and DNA cytometry are cost-effective and robust clinical tests.…”
mentioning
confidence: 99%
“…Several studies have shown that aneuploid tumours are more aggressive than diploid tumours in head and neck cancers (Hogmo et al, 1994;Rubio Bueno et al, 1998). Proliferative activity, as determined by expression levels of the Ki-67 nuclear antigen, has been linked to prognosis and treatment prediction with varying results in oral cancer, with few studies performed exclusively in OTSCC (Xie et al, 1999;Pich et al, 2004;Lothaire et al, 2006;Kim et al, 2007). The use of immunohistochemistry and DNA cytometry are cost-effective and robust clinical tests.…”
mentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the fifth most common cancer worldwide, with a global annual incidence of 780,000 new cases (1). More than 90% of these cancer types have a squamous origin, and common sites include the hypopharynx, larynx, oral cavity, nasopharynx, oropharynx, paranasal sinus, nasal cavity, parathyroid and salivary glands (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Late presentation of the lesion, lack of suitable markers for early detection and failure of advanced lesions to respond to the available chemotherapy contribute to a poor outcome of HNSCC (7). However, loco-regional relapse and metastasis after conventional therapy appear to be significant contributing factors for restricted survival of HNSCC patients (1).…”
Section: Introductionmentioning
confidence: 99%
“…4 The higher expressions of EGFR have been seen to be of prognostic value in head and neck SCC (HNSCC). 5,6 This study may help in indicating that EGFR expressions correlate with the severity of OSCC, and it is also possible that the immunohistochemical (IHC) demonstration of these markers may serve to be a useful prognostic tool for a more precise clinical outcome of OSCC.…”
mentioning
confidence: 99%